Fenomenologi Pendidikan di Perguruan Tinggi Islam: Analisis Problematika dan Solusi - Daulad, Ahmad; Sasralina, Rika; Yahya, Muhammad; Nalus, Syafrul (Al-Ashri: Ilmu-Ilmu Keislaman, 2023)
Islamic Higher Education is an important component in the national education system. Islamic Higher Education has an important role in producing a young generation who has strong Islamic values. However, in reality, Islamic Higher Education management is still not professional. This can be seen from the large number of Islamic Higher Education that have not implemented effective and efficient management. This research aims to analyze the problems of unprofessional Islamic Higher Education management. This research uses a literature study method with an approach phenomenological. Data sources are taken from books, journal articles, research reports, and other sources related to educational problems and solutions in Islamic Higher Education. All data from literature studies are analyzed and solutions are found. Analysis and solutions to these problems can be carried out using a phenomenological approach. The results of the analysis show that there is a solution to the problems of education in Islamic universities. In fact, overcoming the problem lies in increasing the competence of Islamic Higher Education managers, increasing the implementation of an effective and efficient management system, increasing cooperation between Islamic Higher Education and the government and the community, preparing a more relevant curriculum, improving the quality of lecturers and educational staff, providing adequate facilities and infrastructure. The results of this research can be implemented comprehensively and sustainably. The problems at Islamic Higher Education can be overcome and Islamic Higher Education can become a quality educational institution capable of producing quality cadres of national leaders.